2017
DOI: 10.4103/jrpp.jrpp_17_9
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in patients with enteral feeding tubes in the intensive care unit

Abstract: Objective:Most patients admitted to Intensive Care Units (ICU) have problems in using oral medication or ingesting solid forms of drugs. Selecting the most suitable dosage form in such patients is a challenge. The current study was conducted to assess the frequency and types of errors of oral medication administration in patients with enteral feeding tubes or suffering swallowing problems.Methods:A cross-sectional study was performed in the ICU of Shahid Sadoughi Hospital, Yazd, Iran. Patients were assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
(18 reference statements)
4
15
0
Order By: Relevance
“…From a pharmacological point of view, together with previously published results, our findings confirm the existence of important risk areas in critical care related to the administration of medications via NGTs, although the intravenous route is the most widely used in this context [18, 19]; the dose interval of antibiotics [16, 17]; and the dilution, concentration, and infusion speed of high-risk medications [6, 21, 22, 45, 46].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From a pharmacological point of view, together with previously published results, our findings confirm the existence of important risk areas in critical care related to the administration of medications via NGTs, although the intravenous route is the most widely used in this context [18, 19]; the dose interval of antibiotics [16, 17]; and the dilution, concentration, and infusion speed of high-risk medications [6, 21, 22, 45, 46].…”
Section: Discussionsupporting
confidence: 84%
“…Published work has identified certain pharmacological groups as having extensive multicausality error risks; among these, antibacterial drugs are particularly important because of their widespread use and frequency of errors in their use [16, 17]. Another high-risk group are pharmaceuticals that cannot be administered via a nasogastric tube (NGT) [18, 19] as well as high-risk medications in general [6, 20–22]. However, key determinants must first be identified in order to define effective error prevention strategies [10, 23–25].…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate administration of medications by the NGT led to 23 interventions. Crushed pantoprazole gastro-resistant tablets were most often the subject of the CP' s intervention, and this was also observed in other studies [35,36]. The CP suggested to avoid the administration of large particles and www.bjbms.org [37] identified 457 potential interactions in 240 ICU patients, and 25% of DDIs were considered as major (based on the Lexicomp ® and Micromedex ® databases).…”
Section: Discussionmentioning
confidence: 55%
“…Our reported results, which are highly similar to those previously published by the scientific community in regard to the type of error and drugs involved, confirm these findings. The following aspects pose a risk in ICU: nasogastric tube drug administration (Emami et al, 2012;Sohrevardi et al, 2017); errors in the frequency of antibiotic dose regimens (Agalu et al, 2012;Kiekkas et al, 2011;Muroi et al, 2017;Tainter et al, 2018); and dilution, concentration and infusion rate errors with high-risk medications (Esfahani et al, 2016;Sada et al, 2015;Summa-Sorgini et al, 2012).…”
Section: From a Pharmacological Point Of View Significant Risk Arementioning
confidence: 99%
“…On the one hand, antibiotics are one of the most used medication groups in the ICU, and in turn, with which the greatest number of error opportunities is recorded in relation to the administration schedule (Agalu et al, 2012;Camire et al, 2009;Muroi et al, 2017). Likewise, numerous errors have been detected with manipulation of pharmaceutical forms to be administered through nasogastric tubes (Emami et al, 2012;Sohrevardi et al, 2017). Lastly, many studies have identified high-risk medications as responsible of severe ME (Esfahani et al, 2016;Hsaio et al, 2010;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%